Analisis Nilai Chemical Oxygen Demand (COD) Pada Buangan Limbah Cair Pabrik Penyamakan Kulit Dengan Metode Spektrofotometri UV-Vis - Muhammad Hadi Sulhan (STIKes Karsa Husada Garut, 2016)
A factor to define the quality of water is the amount of oxygen that can be used by living organisms in waters. The higher of COD level, the lower amount of oxygen that can be used by the living organisms in the waters. The aim of this research is to determine COD level in leather industry along the river Ciwalen and Cigulampeng. The procedure to determine of COD level based on SNI 06-6989.2-2004. The sampling was used grab sampling method, and the COD level determination was used UV-Vis spectrophotometer. The data showed that wastewater of 1st factory has a COD level amount 1424 mg / L O2 include in categories of high pollution levels, wastewater of 2nd factory has a COD amount 824 mg / L of O2 include in categories of medium pollution levels, wastewater of 3rd factory has a COD value of 394 mg / L of O2 include in categories of low pollution levels and wastewater of 4th factory has a COD value of 404 mg / L of O2 include in categories of low pollution levels.